Fisetin: An Integrated Approach to Identify a Strategy Promoting Osteogenesis - Dalle Carbonare, Luca; Bertacco, Jessica; Gaglio, Salvatore Calogero; Minoia, Arianna; Cominacini, Mattia; Cheri, Samuele; Deiana, Michela; Marchetto, Giulia; Bisognin, Anna; Gandini, Alberto; Antoniazzi, Franco; Perduca, Massimiliano; et al. (Frontiers in Pharmacology, 2022)
Flavonoids may modulate the bone formation process. Among flavonoids, fisetin is known to counteract tumor growth, osteoarthritis as well as rheumatoid arthritis. In addition, fisetin prevents inflammation‐induced bone loss. In order to evaluate its favourable use in osteogenesis, we assayed fisetin supplementation both in vitro and in vivo models and gathered information on nanoparticles-mediated delivery of fisetin in vitro and in a microfluidic system. Rt Real time PCR, Western blotting and nanoparticles synthesis were performed to evaluate the effects of fisetin in vitro, in zebrafish model and in ex vivo samples. Our results demonstrated that fisetin at 2.5 µM concentration promotes bone formation in vitro as well as mineralization in the zebrafish model. In addition, we found that fisetin stimulates osteoblast maturation in cell cultures obtained from cleidocranial dysplasia patients. Remarkably, PGLA nanoparticles increased fisetin stability and, consequently, its stimulating effects on RUNX2 and its downstream gene SP7 expression. Therefore, our findings demonstrated the positive effects of fisetin on osteogenesis and suggest that patients affected by skeletal diseases, both of genetic and metabolic origin, ,may actually benefit from fisetin supplementation.